Pengaruh Dinamika Faktor Lingkungan Terhadap Sebaran Horisontal dan Vertikal Katak - Kurniati, Hellen (Perhimpunan Biologi Indonesia, 2011)
ABSTRACTThe Effect of Environmental Factors on the Horizontal and Vertical Movement of Frogs. Fourenvironmental factors (moon phase, air temperature, water temperature and air humidity) weremeasured to determine the impact of environmental factors on the dynamics of horizontal andvertical spread of the frog Rana erythraea, R. nicobariensis and Occidozyga lima in a wetlandarea of Ecology Park, LIPI Campus Cibinong. Observation was done follows transect line(100 meters long) and set along the edge of the lake where the habitat was more diversecompared to the other sites. Observations were carried out from July to November 2009. Theposition of individual frogs (distance from waterâs edge and height from the ground or water)was recorded and then grouped into intervals of 100 cm distance and height each. Correlationanalysis between the number of individuals per unit distance or height with environmentalfactors was measured using the statistical program SPSS version 16.0. The results of thisstudy proved that the air and water temperature as well as air humidity have significant effecton horizontal and vertical ecological distribution of R. erythraea and R. nicobariensis; whereasfour environmental factors had no impact on horizontal distribution of O. lima. The movementof R. erythraea was strongly positively correlated with air temperature, but strongly negativelycorrelated with air humidity; however the abundance of R. nicobariensis was strongly negativelycorrelated with air temperature and strongly positively correlated with air humidity. Mixedvegetation of species Leerxia hexandra and Eleocharis dulcis at a distance between 0-100 cmfrom the edge of the water and height between 0-100 cm from the ground constituted thepreferred microhabitat of frog species R. erythraea and R. nicobariensis.Key words: Environmental factors, Rana erythraea, Rana nicobariensis, Occidoziga lima,Ecology Park, wetland.